THE DEVELOPMENT OF A MOBILE APPLICATION FOR FRUIT GARDEN TOURISM INFORMATION SYSTEM IN SIDOARJO USING FLUTTER - Mohammad Fadli Zaka; Ade Eviyanti; Yulian Findawati (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: This research highlights the significance of information technology in producing relevant, accurate, and timely information as the foundation for strategic knowledge in decision-making. Applications, as software, play a vital role in presenting information tailored to user needs, based on provided input data. Flutter, serving as an SDK for mobile app development, brings superior capabilities in cross-platform application development. The development of a mobile application for Fruit Garden Tourism Information System in Sidoarjo using Flutter aims to facilitate the search for fruit garden tourism spots based on user preferences and provide detailed information about those locations. The objective is to assist the community in discovering and enjoying fruit garden tourism in Sidoarjo. In the testing process, the black-box method is utilized to identify system weaknesses, validate the congruence of executed data with inputs, and prevent potential deficiencies and errors in the application before user deployment. In the testing process, the application has successfully passed tests for its interface and all provided features with success. Keywords: application; flutter; fruit garden tourism; information technology. Abstrak: Penelitian ini menggambarkan pentingnya teknologi informasi dalam menghasilkan informasi yang relevan, akurat, dan waktu tepat sebagai dasar pengetahuan strategis untuk pengambilan keputusan. Aplikasi, sebagai perangkat lunak, memiliki peran vital dalam menyajikan informasi sesuai dengan kebutuhan pengguna, berlandaskan pada data masukan yang diberikan. Flutter, sebagai SDK untuk pembuatan aplikasi mobile, menghadirkan kemampuan unggul dalam pengembangan aplikasi lintas platform. Pengembangan aplikasi mobile untuk Sistem Informasi Wisata Kebun Buah di Sidoarjo menggunakan Flutter bertujuan memudahkan pencarian tempat wisata kebun buah sesuai preferensi pengguna dan menyediakan informasi yang terperinci tentang lokasi tersebut. Tujuannya adalah memfasilitasi masyarakat dalam menemukan dan menikmati wisata kebun buah di Sidoarjo. Dalam proses pengujian, metode black box digunakan untuk mengidentifikasi kelemahan sistem, memvalidasi kesesuaian data yang dieksekusi dengan yang dimasukkan, serta mencegah potensi kekurangan dan kesalahan dalam aplikasi sebelum digunakan oleh pengguna. Pada proses pengujian, aplikasi telah berhasil melewati pengujian untuk aspek tampilan dan seluruh fitur yang disediakan dengan sukses. Kata kunci: aplikasi; flutter; teknologi informasi; wisata kebun buah.